Shaking Up the Firm Survival: Evidence from Yogyakarta (Indonesia) - Aloysius Gunadi Brata; Henri L. F. de Groot; Wouter Zant (Tinbergen Institute, 2018)
The survival of firms under changes in the business environment caused by exogenous shocks may be explained using economic Darwinism. Exogenous shocks can cause `cleansing effects' as shocks clean out unproductive firms so that available resources are allocated to the remaining more productive firms. However, shocks may also force out young firms that are potentially highly productive in the future, which will lower the average productivity of industries. This is known as the `scarring effect' of shocks. Therefore, the overall impact of exogenous shocks on the allocation of resources depends on the relative magnitude of cleansing and scarring effects. This paper investigates this natural selection mechanism after the Yogyakarta earthquake in 2006. The study uses data on medium-sized and large manufacturing firms in the Yogyakarta province collected by the Indonesian Statistical Agency. The main finding of this paper is that firms that had higher productivity prior to the earthquake in 2006 were more likely to survive after the earthquake, which suggests the existence of a natural selection mechanism causing cleansing effects. There is no evidence of scarring effects of the earthquake on the new entrants.
Keywords: D22; Q54; R11; 330; firm's survival; exogenous shock; Yogyakarta earthquake; Indonesia